INDONESIAN STUDENTS' ERROR IN THE USE OF DETERMINERS - Tyas Gita Atibrata (Universitas Gadjah Mada, 2012)
This research attempts to investigate Indonesian students' errors in the use of determiners in their English writing. More specifically, it is an attempt to identify Gadjah Mada University English Department students' errors in the use of English determiners and classify them according to the types of determiners and the structural change of determiners. The results of the research shows that most of the incorrect use of the determiners was in the form of articles with 71 cases (72.44%), followed by possessives 12 (12.24%), demonstratives 10 (10.20%), and quantifiers 5 cases (5.10%). The results seem to suggest that the students had the greatest difficulty in the use of articles in writing in English. However, they did not seem to have difficulty in the use of demonstratives, possessives, and quantifiers. The incorrect use of determiners some structural alteration of the determiners. There are five types of stuructural alteration of determiners: addition, omission, misorder, misformation, and misuse. Most of them were omission with 29 (29.59%). All of them were in the form of articles, followed by misformation with 28 cases (28.57%), addition with 19 cases (19.38%), misuse with 14 cases (14.28%), and misordering with 8 cases (8.16%). The results suggest that most of the students tend to omit the articles in their writing.